2019
DOI: 10.1021/acs.inorgchem.9b00822
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic and Theoretical Studies of the 3d Transition Metal Oxyfluoride Molecules

Abstract: A collection of 3d transition metal (V, Mn, Fe, Co, and Ni) oxyfluorides were prepared via the reactions of laser-ablated metal atoms and OF2 in an argon matrix, and the products were identified by infrared spectroscopy together with 18OF2 substitution. OMF2 is the major product from the reactions of metal atoms and OF2. The tetravalent metal center is coordinated to two fluorine atoms and one oxygen atom. Triatomic OMF molecules were observed in the reactions of V, Mn, Fe, and Co with OF2. In addition to OMF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 90 publications
2
13
0
Order By: Relevance
“…Unlike most of the works that report CASPT2 geometry optimization that were focused on organic molecules, a series of papers by Andrews and coworkers [98][99][100][101][102][103][104] explored the electronic structure of small actinide and transition metal complexes in noble gas matrices. These studies demonstrated the importance and applicability of CASPT2 for geometry optimization and harmonic vibrational frequencies calculations, using numerical gradients and numerical Hessian calculations available in molcas.…”
Section: B Perturbation Theory Applications: Numerical Gradientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike most of the works that report CASPT2 geometry optimization that were focused on organic molecules, a series of papers by Andrews and coworkers [98][99][100][101][102][103][104] explored the electronic structure of small actinide and transition metal complexes in noble gas matrices. These studies demonstrated the importance and applicability of CASPT2 for geometry optimization and harmonic vibrational frequencies calculations, using numerical gradients and numerical Hessian calculations available in molcas.…”
Section: B Perturbation Theory Applications: Numerical Gradientsmentioning
confidence: 99%
“…30 The species that were studied include N≡UF 3 and P≡UF 3 ; 98 FB=ThF 2 ; 101 N≡U=N-H; 102 SUO and US 2 ; 103 halomethanes with laser-ablated nickel, palladium, and platinum; 99,100 and 3d transition metal oxyfluoride molecules. 104 The numerical gradient implementations of CASPT2 and XMCQDPT2 remain in widespread use for optimizing molecular structures. Notable examples include locating equilibrium geometries and conical intersections with MS-CASPT2 in 2011, 46 locating equilibrium geometries and conical intersection in acetophenone with XMCQDPT2 in 2013, 52 locating equilibrium geometries, conical intersections, transition state geometries, and reaction pathways of thymine with MS-CASPT2 in 2016, 60 locating equilibrium geometries of various RPSB models in 2017, 65 generating a benchmark set of excited-state geometries of organic molecules with MS-CASPT2 in 2017, 67 and optimizing equilibrium structures and crossing points in 2-selenouracil in 2019.…”
Section: B Perturbation Theory Applications: Numerical Gradientsmentioning
confidence: 99%
“…In our argon matrix isolation experiments, the absorptions of the OMnF 2 molecule were observed (Table 1) at 928.0 and 757.0 cm −1 , respectively, which have been reported with the same values for the reaction of Mn with OF 2 in solid argon. 13 The neon−argon matrix shifts of the stretching modes are smaller (8.3 cm −1 reduction) for the more covalent Mn−O bond and larger (12.8 cm −1 ) for the almost purely ionic Mn−F bond. Notably, these absorptions of OMnF 2 in solid argon are very different from some previously reported values.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In our argon matrix experiments, the absorptions of the OFeF 2 molecule were detected at 882.5 and 761.3 cm −1 , which are the same as the values observed in Fe atom reactions with OF 2 in solid argon. 13 The B3LYP DF calculations on the free molecules yielded the MO stretching wavenumbers +6.7% (M = Mn) and +4.4% (M = Fe) too high and the antisymmetric FMF modes −0.4% and −0.7%, respectively, too low (Table 2). Note that the vibrations dominated by ionic M−F interactions are rather accurately reproduced, while the modes dominated by the more covalent M−O interactions are slightly overestimated as usual.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation